1997
DOI: 10.1111/j.1398-9995.1997.tb00185.x
|View full text |Cite
|
Sign up to set email alerts
|

IgE responses to Dermatophagoides pteronyssinus native major allergens Der p 1 and Der p 2 during long‐term specific immunotherapy

Abstract: We investigated by ELISA the IgE response to whole extract of the house-dust mite Dermatophagoides pteronyssinus (Dp) and to the native major allergens, Der p 1 and Der p 2, in sera from 18 adult patients (group A) with Dp-allergic asthma before (t0) and 1, 2, 3, and 4 (t1-t4) years after subcutaneous specific immunotherapy (SIT). A qualitative reduction (P = 0.05) of the IgE responses to Dp and Der p 2 was observed from t1 to t4, but a highly statistical significant decrease appeared at t3 (P < 0.01). With re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
1

Year Published

2001
2001
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 17 publications
1
8
0
1
Order By: Relevance
“…In addition, it was observed a tendency of increased IgE levels to Der p2, demonstrating that children were more sensitized to Der p2 than Der p1. Accordingly, previous studies showed that IgE levels against Der p2 were always higher than those against Der p1 in patient sera, confirming that Der p2 is a more immunologically active molecule than Der p1 in inducing IgE synthesis [19, 20]. On the other hand, specific salivary IgE levels were undetectable in both allergic and nonallergic children, confirming previous report that IgE antibodies were not found in saliva [21].…”
Section: Discussionsupporting
confidence: 83%
“…In addition, it was observed a tendency of increased IgE levels to Der p2, demonstrating that children were more sensitized to Der p2 than Der p1. Accordingly, previous studies showed that IgE levels against Der p2 were always higher than those against Der p1 in patient sera, confirming that Der p2 is a more immunologically active molecule than Der p1 in inducing IgE synthesis [19, 20]. On the other hand, specific salivary IgE levels were undetectable in both allergic and nonallergic children, confirming previous report that IgE antibodies were not found in saliva [21].…”
Section: Discussionsupporting
confidence: 83%
“…Specific IgE and IgG4 to Der p 1 and Der p 2 were measured in serum samples before and after treatment by direct ELISA according to the method of Mastrandrea et al [18], with modifications. Briefly, purified natural Der p 1 and Der p 2 allergens (Indoor Biotechnologies) were dissolved in carbonate/bicarbonate buffer, pH 9.6, at a concentration of 1 µg/ml.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, a previous study found that long-term subcutaneous specific immunotherapy with native allergens Der p1 and Der p2 decreased serum specific IgE and asthma symptoms in patients. 25 Therefore, oral feeding with whole allergen is feasible with regard to specific immunotherapy for asthma.…”
Section: Discussionmentioning
confidence: 99%